The association between chronic obstructive pulmonary disease and autoimmune diseases: a bidirectional Mendelian randomization study - Yu, Xiaohui; Cheng, Xue; Lv, Lin; Wang, Na; Li, Mengcong; Ji, Wenwen; Liu, Tingting; Wang, Guangdong; Hu, Tinghua; Shi, Zhihong (Frontiers in Medicine, 2024)
Objective Observational studies have reported that chronic obstructive pulmonary disease (COPD) is often accompanied by autoimmune diseases, but the causal relationships between them remain uncertain. In this Mendelian study, we aimed to investigate the potential causal relationship between COPD and four common autoimmune diseases. Methods We conducted an analysis of summary data on COPD and autoimmune disease using publicly available genome-wide association studies (GWAS) summary data. We initially employed the inverse- variance weighted method as the primary approach to establish the causal impact of COPD on autoimmune diseases in the sample and conducted additional sensitivity analyses to examine the robustness of the results. Subsequently, we performed reverse Mendelian randomization (MR) analyses for the four autoimmune diseases. Finally, the potential for bidirectional causal relationships was assessed. Results Our MR analysis revealed no significant causal relationship between COPD and any of the studied autoimmune diseases. However, reverse MR results indicated a significant association between rheumatoid arthritis (RA), osteoarthritis (OA) and the risk of developing COPD, with respective odds ratios (OR) of 377.313 (95% CI, 6.625–21487.932, P = 0.004) for RA and 11.097 (95% CI, 1.583–77.796, P = 0.015) for OA. Sensitivity analyses confirmed the robustness of the results. Conclusion Our findings support a potential causal relationship between autoimmune diseases and COPD, highlighting the importance of considering comorbidities in clinical management of COPD.